Chemical profiling of Fritillariae thunbergii Miq prepared by different processing methods reveals two new quality markers: Zhebeininoside and imperialine-3-β-D-glucoside. (30th January 2022) - Shi, Yu-Hua; Huang, Qin-Wei; Zhu, She-Min; Zhou, Yue-Mei; Zhang, Li-Jiang; Huang, Wen-Kang; Shao, Jin-Jin; Zhou, Jian-Liang; Zhang, Wen-Ting
Abstract: Ethnopharmacological relevance: Fritillariae thunbergii Miq (FTM)exhibit versatile biological activities including the significant antitussive and expectorant activities. As a herbal medicine, the therapeutic effects of FTM may be expressed by multi-components which have complicated integration effects on multi-targets. With the time going, the different processing methods of FTM has been changed a lot. Thus，the study described the effect of processing methods to FTM and its quality. Material and method: Studies were undertaken by using UHPLC-LTQ Orbitrap MS and pharmacodynamic models. All reagents were involved of analytical grade. While a HPLC-ELSD's method has been developed and validated, a certified Quality System is conformed to ICH requirements. The experimental animals followed the animal welfare guidelines. Aim of the study: We aimed to found the differences after the different processing methods of FTM, and to demonstrate the changes could be selected as quality control indicators, and established a method for simultaneous determination of these for quality control. Results: we have previously found two new steroidal alkaloids: zhebeininoside and imperialine-3-β-D-glucoside from the different processing methods of FTM, which is the difference between the different processing methods of FTM, mainly on the steroidal alkaloids. The activity analysis of zhebeininoside, imperialine-3-β-D-glucoside, verticine and verticinone showed that the mouse model of cough expectorant has antitussive effect. The positive drug selected was dextromethorphan syrup. The positive group showed biological activity, but the blank group showed nothing. The model group showed illness which means that the model was effective. There are two ways of the mechanism of action of the expectorant action which can make sputum thin, reduce its viscosity, and be easy to cough up, or can accelerate the movement of mucous cilia in the respiratory tract and promote the discharge of sputum. In our study, the content of phenol red was significantly reduced in the administration group. Conclusions: To sum up, our results suggest that zhebeininoside and other three components cloud be selected as quality control indicators, and a method for simultaneous determination of zhebeininoside and other three components was established for quality control. Graphical abstract: Image 1